PAR 2021
DOI: 10.20517/2347-9264.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling with injectable platelet-rich fibrin for facial rejuvenation

Abstract: Aim:The aim of this literature review is to evaluate the efficacy of microneedling treatment with injectable plateletrich fibrin (i-PRF) for facial skin rejuvenation applications, using an objective skin analysis system and validated patient-reported outcome measures. Methods:The search approach involved the exploration of electronic databases. An advanced search option was applied to filter our search line, i.e., from February 2011 to April 2021. We performed a search on Medline, Scopus, Embase, and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Growth factor binding and platelet capture are facilitated via the three-dimensional fibrin structure of PRF that results in the enhancement of the gradual and long-term release of cytokines and growth factors. Moreover, this fibrin mesh is also responsible for cell proliferation and differentiation and the formation of new blood vessels [ 11 , 12 ]. Finally, PRF prompts cell proliferation, migration, differentiation, and adhesion accompanied by anti-inflammatory properties that further support its therapeutic aptitude in bone regeneration, wound healing, improving scar appearance, and stimulating hair growth [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth factor binding and platelet capture are facilitated via the three-dimensional fibrin structure of PRF that results in the enhancement of the gradual and long-term release of cytokines and growth factors. Moreover, this fibrin mesh is also responsible for cell proliferation and differentiation and the formation of new blood vessels [ 11 , 12 ]. Finally, PRF prompts cell proliferation, migration, differentiation, and adhesion accompanied by anti-inflammatory properties that further support its therapeutic aptitude in bone regeneration, wound healing, improving scar appearance, and stimulating hair growth [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these platelet aggregate products contain cell adhesion proteins PRF, the second generation of platelet concentrates, is superior to PRP in numerous aspects. First of all, PRF preparation consists of only one centrifugation step, making it simpler than PRP preparation [12]. As a result of declined centrifuge speed, PRF has been observed to contain higher volumes of growth factors, leukocytes, fibrin, and platelets than PRP, resulting in a more boosted growth factor-mediated functional aftermath [11].…”
Section: P a T I E N T 1 R P A T I E N T 1 L P A T I E N T 2 R P A T ...mentioning
confidence: 99%
“…The morphology of i-PRF is retained for more than 10 days. 12,13 The lower adjustment of the relative centrifugation force (RCF) while preparing PRF matrices increases platelet (with meaningfully higher concentrations of major growth factors) and White Blood Cells counts in the resultant PRF matrix to a great extent. [14][15][16][17] The lower RCF protocol (60 g) and higher RCF protocol (208 g) generate 2 different types of matrices.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] The lower RCF protocol (60 g) and higher RCF protocol (208 g) generate 2 different types of matrices. 12 In the authors' study, the authors used the low RCF protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The growth factors in PRF are known to stimulate collagen production, which is crucial in maintaining skin elasticity and strength, thereby potentially reducing wrinkles and improving skin texture [8,9]. Clinical trials and cohort studies have shown promising results in using PRF for facial esthetic improvements, including reducing the appearance of wrinkles and fine lines [10,11]. Despite these promising applications, the evidence is still emerging, and the mechanisms by which PRF exerts its effects still need to be fully understood.…”
Section: Introductionmentioning
confidence: 99%